2004
DOI: 10.1021/jf049388y
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Induced Redistribution of Disulfide Bonds in Milk Proteins. 1. Bovine β-Lactoglobulin

Abstract: Changes in the structure and chemistry of beta-lactoglobulin (beta-LG) play an important role in the processing and functionality of milk products. In model beta-LG systems, there is evidence that the aggregates of heated beta-LG are held together by a mixture of intermolecular non-covalent association and heat-induced non-native disulfide bonds. Although a number of non-native disulfide bonds have been identified, little is known about the initial inter- and intramolecular disulfide bond rearrangements that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
97
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 27 publications
11
97
0
Order By: Relevance
“…Cys106 seems to be always involved in different disulfide bonds, 384 while the other four cysteine residues reacted with IAEDANS indicating that they 385 were sometimes generated in free sulfhydryl form following sulfhydryl/disulfide 386 exchange reactions. In addition to the role of Cys160 as a major player of 387 sulfhydryl/disulfide exchange reaction [10], results obtained highlight the prevalent 388 occurrence of Cys66 as an exposed cysteine under our conditions of heat-treatment. 389 534 535 536 537 538 539 540 541 542 543 544 545 546 547 548 549 550 551 552 553 554 555 556 557 558 559 …”
Section: Cys160 (Peak 2) 308mentioning
confidence: 78%
See 1 more Smart Citation
“…Cys106 seems to be always involved in different disulfide bonds, 384 while the other four cysteine residues reacted with IAEDANS indicating that they 385 were sometimes generated in free sulfhydryl form following sulfhydryl/disulfide 386 exchange reactions. In addition to the role of Cys160 as a major player of 387 sulfhydryl/disulfide exchange reaction [10], results obtained highlight the prevalent 388 occurrence of Cys66 as an exposed cysteine under our conditions of heat-treatment. 389 534 535 536 537 538 539 540 541 542 543 544 545 546 547 548 549 550 551 552 553 554 555 556 557 558 559 …”
Section: Cys160 (Peak 2) 308mentioning
confidence: 78%
“…Exposed sulfhydryl groups are further able to react with other proteins 69 leading to the formation of dimers, oligomers and larger aggregates [3,4,7]. When 70 the dimers and trimers were digested with trypsin and analyzed by mass spectrometry 71 in MALDI and electrospray modes, it was found that several new disulfide bonds 72 were formed: Cys121-Cys160, Cys106/119/121-Cys160, as well as an intermolecularthat its release following sulfhydryl/disulfide exchange reactions is an important step 77 to propagate intermolecular exchange reactions [10]. Determining which sulfhydryl 78 groups are exposed on heating (important contributors for sulfhydryl/disulfide 79 interchange reactions) will give a greater insight into mechanism of how the 80 sulfhydryl/disulphide exchange reactions proceed.…”
Section: Introduction 52mentioning
confidence: 99%
“…The disulfide bridges are known to be a key factor that affects the gel strength (Hoffmann and Van Mil, 1999;Creamer et al, 2004) and the aggregation process through the polymerization of monomers to form large polymer chains. However, there is only limited availability of the bonds to be formed and hence excessively longer heating time may not be effective anymore.…”
Section: Effect Of Heating Time On Hiwpg Dissolutionmentioning
confidence: 99%
“…Each monomer has a molecular weight of 18.3 kDa, contains 162 amino acid residues, two disulphide bonds (C106-C119 and C66-C160) and one free cysteine residue (C121) [6][7][8] . Upon heating, betalactoglobulin dissociates into monomers, leading to exposure of hydrophobic groups and the free sulfhydryl group [9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation of beta-lactoglobulin occurs mainly via intermolecular disulphide bond exchange, i.e. the aggregation is not (in the main) due to nucleationdependent processes [7,9] but arises from polymerization. In a previous study [21] indicated that alpha-crystallin did not inhibit the aggregation of a serpin (AT (antitrypsin)) which aggregated via a polymerization reaction but did inhibit a serpin aggregation (ACT (antichymotrypsin)) when occurring via a nucleation-dependent mechanism.…”
Section: Introductionmentioning
confidence: 99%